Evaluation of the Level of Knowledge of Housewives Regarding How to Store Medicines in Galesong Village, Takalar Regency (International Forum of Researchers and Lecturers, 2025)
Proper medication storage ensures the safety and effectiveness of drugs, while appropriate destruction practices are vital to prevent the risks associated with expired or poor-quality medications. At the household level, correct drug management helps avoid medication errors, environmental pollution, and potential misuse. This study aimed to examine how housewives in Galesong Village, Takalar Regency, handle drug storage and destruction. A non-experimental quantitative method was used, with data collected in numerical form through structured questionnaires. Respondents were selected via purposive sampling, based on inclusion criteria such as being between 18–50 years old, having experience in drug storage and disposal, possessing good communication skills, not working in healthcare, and providing informed consent. From a population of 3,633 residents, a sample size of 100 housewives was determined using the Slovin formula. The results showed that the majority (86.3%) of participants demonstrated a good level of knowledge regarding proper drug storage. However, knowledge related to drug destruction was found to be moderate among 67.8% of respondents. These findings suggest that while housewives in the area are generally well-informed about how to store medications safely, there is still a need to improve awareness and understanding of safe drug disposal methods. Therefore, public health initiatives, especially those focusing on education and community outreach, are essential to strengthen drug management practices at the household level. By enhancing awareness in both areas—storage and destruction—households can contribute more effectively to medication safety and environmental protection, ultimately promoting better health outcomes for the broader community.